2022
DOI: 10.1021/acs.langmuir.1c02626
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Dissolved Gas on the Interfacial Properties of Decane Surface Nanodroplets

Abstract: Surface nanodroplets have received extensive attention recently due to their potential in the fabrication of functional materials with nanostructures and chemical reactions at micro-and nanoscales. Although the effect of dissolved gas in water has been realized in some important processes such as spontaneous emulsification of oil droplets in water, its roles in the wetting behavior of surface nanodroplets at the hydrophobic interface have been largely neglected. Here, we focused on the influence of dissolved g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It is known that dissolved gas acts as a surfactant and that surface tension is reduced with more soluble gas. , Lee et al demonstrated that surface tension of water decreased considerably by increasing the DO content to 46 ppm. Geng et al proposed the mechanism of decrease in surface tension of oil nanodroplets in water, which is analogous to gas-filled NBs. These facts indicate that the influence of dissolved gas is not negligible under extremely high DO level conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that dissolved gas acts as a surfactant and that surface tension is reduced with more soluble gas. , Lee et al demonstrated that surface tension of water decreased considerably by increasing the DO content to 46 ppm. Geng et al proposed the mechanism of decrease in surface tension of oil nanodroplets in water, which is analogous to gas-filled NBs. These facts indicate that the influence of dissolved gas is not negligible under extremely high DO level conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the discrepancy is that bulk nanobubbles are a special kind of Janus particles, like chemically modified Janus particles, which reduce surface tension of water much more significantly than normal Janus particles . With regard to the influence of dissolved gases in the liquid, it has been known that any solutes could reduce the surface tension of water by increasing the translational entropy at the liquid’s surface, which results in the decrease in free energy of the liquid’s surface per unit area, equivalent to surface tension. , Accordingly, gases dissolved in liquid water reduce surface tension, as experimentally reported. However, according to the experiments, a considerable reduction in surface tension occurs only under the very high supersaturation of gases in liquid water. In the Tuziuti et al experiment, surface tension was measured for liquid water containing bulk nanobubbles under an almost saturated condition of air.…”
Section: Resultsmentioning
confidence: 99%
“…It was then placed in a vacuum-drying oven, degassed to below 0.1 atm, and held for more than 10 h. All degassing processes were repeated three times. 55,56 Generation of Bulk NBs. A detailed description of the generation of bulk NBs by the compression−decompression method is provided in the previous literature.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Nanoparticle tracking analysis (NTA) was used to measure the size distribution and concentration of NBs. The instrument used in the experiments was a Malvern NanoSight series instrument, model NS300, with NanoSight V3.4 software, which was capable of characterizing nanoparticles in the range of 10–2000 nm in different kinds of solutions by tracking the Brownian motion of the nanoparticles in real time and obtaining their concentration, particle size, and other relevant information …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation